Characterisation of mechanical responses of nickel based superalloys to deformation at high strain rates and high temperatures - Wilson, H (2018)
The project established an understanding on the mechanical and microstructural characteristics of two Nickel based superalloys, RR1000 and IN718 under high strain rate deformation at elevated temperatures. The strain rates tested are from 0.5s−1 up to 3000s−1 and the temperatures from 700◦C up to 1200◦C at 100◦C intervals, with a heating rate of 100◦Cs−1 or 50◦Cs−1 at higher temperatures. These conditions are selected to closely resemble the conditions seen in inertia friction welding. It was found that both yield and peak stresses of RR1000 and IN718 are relatively independent of strain rates, but decrease with increasing temperatures. Both materials harden significantly below 700 ◦C, and the work hardening decreases with increasing temperature but remains relatively independent of strain rates, as a result of the excellent precipitation hardening effect from the γ' and γ''in RR1000 and IN718 respectively. RR1000 work hardens considerably more than IN718, which is attributed to twinning observed in both γ matrix and γ' precipitates, whereas twinning only occurs in the γ matrix in IN718. At high temperatures, particularly just below the solvus temperature, the adiabatic temperature rise at high strain rate can be sufficient to push the deformation above the solvus temperature. Therefore, the mechanical strength of the material is significantly decreased, from not only the further dissolution of strengthening γ' precipitates, but also from constitutional liquation of the remaining γ' precipitates. As the deformation continues, dynamic recrystallisation of grains occurs in the microstructure, which softens the material. This process occurs at a critical strain, which decreases with increasing temperature but increases with increasing strain rates. Therefore, the mechanical strength of RR1000 and IN718 at high strain rates and high temperature is dependent on the competition between the hardening of precipitates and twinning in the microstructure, and the softening from the adiabatic temperature rise, as well as the dynamic recrystallisation of the grains during plastic deformation.